2006
DOI: 10.1071/is05020
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Nicrophorus in part: new species and inferred phylogeny of the nepalensis-group based on evidence from morphology and mitochondrial DNA (Coleoptera:Silphidae:Nicrophorinae)

Abstract: Carrion beetles of the genus Nicrophorus Fabricius, 1775 (Silphidae) are well known for their biparental brood care and monopolisation of small vertebrate carcasses in subterranean crypts. Although the taxonomy of New World species has received modern attention, the fauna of Asia, primarily of the nepalensis-group of species, has not. Herein we revise this species-group and describe as new the following seven species: Nicrophorus charon Sikes & Madge (Sulawesi), . We obtained a preliminary phylogeny using morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 80 publications
(100 reference statements)
0
21
1
Order By: Relevance
“…Species of this group are primarily montane in regions of eastern Asia and the Malay Archipelago, ranging in longitude from 73°E (Pakistan) to 160°E (Guadalcanal) and latitude from 51°N (Ussuri, Russia) to 9°48'S (Papua New Guinea) (Sikes et al 2006). In the first descriptions of the species group, Portevin (1926), who originally aligned its members, and Hatch (1927), who formally recognized the species group, included five species: Nicrophorus nepalensis Hope, Nicrophorus podagricus Portevin, Nicrophorus heurni Portevin, Nicrophorus quadripunctatus Kraatz, and Nicrophorus maculifrons Kraatz.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Species of this group are primarily montane in regions of eastern Asia and the Malay Archipelago, ranging in longitude from 73°E (Pakistan) to 160°E (Guadalcanal) and latitude from 51°N (Ussuri, Russia) to 9°48'S (Papua New Guinea) (Sikes et al 2006). In the first descriptions of the species group, Portevin (1926), who originally aligned its members, and Hatch (1927), who formally recognized the species group, included five species: Nicrophorus nepalensis Hope, Nicrophorus podagricus Portevin, Nicrophorus heurni Portevin, Nicrophorus quadripunctatus Kraatz, and Nicrophorus maculifrons Kraatz.…”
Section: Introductionmentioning
confidence: 99%
“…Sikes (2003) removed Nicrophorus sausai , but added Nicrophorus apo Arnett and Nicrophorus insularis Grouvelle. The most recent taxonomic and phylogenetic work on the nepalensis species group is that by Sikes et al (2006) who included seven newly described species, bringing the total number of species in the group to 15.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that this more extensive darkening may be associated with wooded habitats. Latitude and longitude references for the type localities are, for Tatsienlu Tjiji 30°25' (=30.417°) N 102°40'(=102.667°) E (Balke 1992) and for Mukue Tatsienlu 30.05°N 102.03°E (Sykes et al 2006). Google Earth gives altitudes of 1944 m a.s.l.…”
Section: Resultsmentioning
confidence: 99%